2020
DOI: 10.1371/journal.pone.0233840
|View full text |Cite
|
Sign up to set email alerts
|

IMRAS—A clinical trial of mosquito-bite immunization with live, radiation-attenuated P. falciparum sporozoites: Impact of immunization parameters on protective efficacy and generation of a repository of immunologic reagents

Abstract: Background Immunization with radiation-attenuated sporozoites (RAS) by mosquito bite provides >90% sterile protection against Plasmodium falciparum (Pf) malaria in humans. RAS invade hepatocytes but do not replicate. CD8+ T cells recognizing parasite-derived peptides on the surface of infected hepatocytes are likely the primary protective mechanism. We conducted a randomized clinical trial of RAS immunization to assess safety, to achieve 50% vaccine efficacy (VE) against controlled human malaria infection (CHM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(57 citation statements)
references
References 52 publications
2
55
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted July 29, 2021. ; https://doi.org/10.1101/2021.07.28.454252 doi: bioRxiv preprint early timepoints, suggesting that Th1 responses contribute to PfRAS vaccination-induced immunity. This is consistent with studies in animal models which concluded that sterilizing protection involves Th1 cells which secrete IFNγ and, in co-ordination with with macrophages and liver resident cytotoxic CD8 T cells, eliminate intracellular pathogens (Cockburn et al, 2013;Fernandez-Ruiz et al, 2016a;Hickey et al, 2020;McNamara et al, 2017;Tse et al, 2014)(Perez-Mazliah andLanghorne, 2014). In addition, the correlation of CSP-specific, IFNγ-producing CD4 T cells with protection from infection following RTS,S/AS02 vaccination (Reece et al, 2004) also suggests that Th1 cells can contribute protective immunity in humans.…”
Section: Innate Priming Of Naïve T Cells Into Various T-helper Cells Can Occur Through the Actions Ofsupporting
confidence: 90%
See 3 more Smart Citations
“…The copyright holder for this preprint (which this version posted July 29, 2021. ; https://doi.org/10.1101/2021.07.28.454252 doi: bioRxiv preprint early timepoints, suggesting that Th1 responses contribute to PfRAS vaccination-induced immunity. This is consistent with studies in animal models which concluded that sterilizing protection involves Th1 cells which secrete IFNγ and, in co-ordination with with macrophages and liver resident cytotoxic CD8 T cells, eliminate intracellular pathogens (Cockburn et al, 2013;Fernandez-Ruiz et al, 2016a;Hickey et al, 2020;McNamara et al, 2017;Tse et al, 2014)(Perez-Mazliah andLanghorne, 2014). In addition, the correlation of CSP-specific, IFNγ-producing CD4 T cells with protection from infection following RTS,S/AS02 vaccination (Reece et al, 2004) also suggests that Th1 cells can contribute protective immunity in humans.…”
Section: Innate Priming Of Naïve T Cells Into Various T-helper Cells Can Occur Through the Actions Ofsupporting
confidence: 90%
“…The IMRAS cohort analyzed consisted of eleven malaria-naïve adults immunized with five doses of approximately 200 bites from Pf RAS NF54 infected mosquitos (Hickey et al, 2020). The first four doses were given four weeks apart and the final dose was administered five weeks after the fourth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A pediatric formulation of RTS,S/AS01 is currently undergoing Phase 4 trials at several field sites across Africa 10 . Immunization via mosquito bite with radiation-attenuated sporozoites (IMRAS vaccine) 11 , cryopreserved irradiated sporozoites (PfSPZ vaccine) 12 or sporozoites delivered under chloroquine prophylaxis (PfSPZ-C vaccine) 13 also elicit protection against CHMI that is in part mediated by inhibitory CSP antibodies. Highly protective polyclonal and monoclonal antibodies have been mapped to the central repeats and junctional sequence, but not to the N- or C-terminal regions of CSP 2 , 14 16 .…”
Section: Introductionmentioning
confidence: 99%